2013 IEEE International Conference on Systems, Man, and Cybernetics 2013
DOI: 10.1109/smc.2013.557
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Quality Metrics for 3D Meshes: Towards an Optimal Multi-attribute Computational Model

Abstract: Abstract-3D graphical data, commonly represented using triangular meshes, are deployed in a wide range of application processes including compression, filtering, watermarking, and simplification. These processes often introduce geometric distortions which affect the visual quality of the ultimate data visualization. In order to accurately evaluate perceptual impacts caused by the distortions, assessment metrics on 3D Mesh Visual Quality (MVQ) have been extensively discussed in the literature. Researchers recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Even small inaccuracies in position can have a noticeable effect on the appearance of a model when rendered with direct lighting or a texture map. Lavoue et al (2013) have assessed computational measures of curvature and roughness similarity and reported that mean curvature and geometric Laplacian metrics correlate well with visual perception metrics. We have implemented the same measures in our pipeline and observed a similar agreement between these two metrics and visual inspection of surface smoothness, as shown in Table 6.…”
Section: Curvature and Roughness Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even small inaccuracies in position can have a noticeable effect on the appearance of a model when rendered with direct lighting or a texture map. Lavoue et al (2013) have assessed computational measures of curvature and roughness similarity and reported that mean curvature and geometric Laplacian metrics correlate well with visual perception metrics. We have implemented the same measures in our pipeline and observed a similar agreement between these two metrics and visual inspection of surface smoothness, as shown in Table 6.…”
Section: Curvature and Roughness Metricsmentioning
confidence: 99%
“…Source imagery and ground truth data used for experiments have also been publicly released in the Multi-View Stereo 3D Mapping Challenge (MVS3DM) Benchmark (2017). 3D model evaluation metrics in our pipeline include horizontal and vertical accuracy and completeness (similar to metrics employed by Akca et al 2010, Bosch et al 2016, and Sampath et al 2014, volumetric completeness and correctness (similar to work reported by McKeown et al 2000), perceptual quality (based on the work of Lavoue et al 2013), and model simplicity (a relative measure of triangle or geon count). These metrics are intended to expand upon the multiple view stereo analysis by Bosch et al (2016) and enable a comprehensive automated performance evaluation of both geometric and perceptual value of 3D object models reconstructed from imagery as well as assessment of the modeling process at the point cloud reconstruction, semantic labeling, and mesh simplification or model fitting steps.…”
Section: Introductionmentioning
confidence: 97%
“…curvature computations [45,42,86], dihedral angles [18,89], Geometric Laplacian [32,84], and Laplacian of Gaussian curvature [97]. Lavoué et al [43] have hypothesized that a combination of these attributes could deliver better results that using them separately. They propose a quality metric based on an optimal linear combination of these attributes determined through machine learning.…”
Section: Model-based Metricsmentioning
confidence: 99%
“…Table 1 summarizes these correlation results; best metrics are highlighted for each database. Note that many metrics cannot be applied to evaluating simplification distortions because they need the compared objects to share the same connectivity - [32,84,45,89,43] -or the same level of details - [18]. Table 1 Correlation between Mean Opinion Scores and values from the metrics for four publiclyavailable subjective databases.…”
Section: D Model Quality Assessmentmentioning
confidence: 99%
“…The image quality assessment community has conducted significant studies on using machine learning techniques to support IVQ assessment [11]- [17], while most existing mesh quality assessment approaches [1]- [6] attempt to model the HVS explicitly. Lavoue et al [18] proposed a perceptual evaluation metric based on multiple attributes using machine learning techniques. This metric did not take the characteristics of HVS into account, and cross-database performance was not presented to justify its generalization capability.…”
Section: Introductionmentioning
confidence: 99%